Innovative Model of Agricultural Supply Chain Distribution to Strengthen Vegetable Farmers' Income: A Case Study of Tarubatang Village - Sujatmiko, Sujatmiko; Budiarto, Budiarto; Lakasana, Dwi Hari (RSF Conference Series: Business, Management and Social Sciences, 2025)
The agricultural supply chain plays an important role in determining farmers’ income, particularly in the horticultural subsector, which is highly sensitive to distribution speed and market dynamics. However, vegetable farmers in Tarubatang Village, Selo District, Boyolali, still face a lengthy distribution chain dominated by intermediaries, resulting in low selling prices and weak bargaining positions. This study aims to analyze the influence of distribution efficiency on farmers’ income and to formulate an innovative, fair, and sustainable distribution model. A quantitative approach was employed, utilizing a survey method that involved 30 farmers, complemented by in-depth interviews and observations. The interview data were analyzed using qualitative techniques to identify farmers’ perceptions of distribution patterns and the constraints faced within the supply chain. Quantitative data were analyzed using descriptive statistics and simple linear regression. The results indicate that distribution efficiency has a positive and significant impact on farmers’ income (p < 0.05), accounting for 46% of the variation in income due to distribution-related factors. On average, farmers' incomes increased by 37% following the implementation of distribution models based on farmer group institutions and digital marketing. These findings confirm that integrating farmer groups with digital platforms can shorten the distribution chain, increase price transparency, and strengthen farmers’ bargaining positions. The practical implications of this study highlight the need for local government support to strengthen farmer institutions and enhance access to digital technology, thereby achieving efficient and sustainable agricultural distribution.